EXAMINING THE EFFECT OF RECREATIONAL ACTIVITIES ON UNIVERSITY STUDENTS’ SELF-ESTEEM - Korkmaz YİĞİTER; İhsan Sarı; Yıldız Öztan Ulusoy; Fikret Soyer (Sport Scientific And Practical Aspects, 2025)
The aim of this research was to find out the effect of 12-weeks recreational activities on university students’ self-esteem. For this purpose, 40 students from Health Service High-School of Düzce University participated to the study. Experimental group consisted of 20 students and another 20 students were in the control group. Cooper Smith Self-esteem Inventory which was developed by Stanley Coopersmith (1967) was used in the study. Data analysis was made by SPSS 16.0. Descriptive statistics, independent sample t-test, paired sample t-test and Pearson’s correlation analysis were used to analyze the data. Level of significance was 0.05. After pre-test, experimental group joined 12-weeks recreational activities which was one day in a week and lasted 2 hours. Recreational activities consisted of salon football, volleyball, swimming and various educational games. Post-test application was made after 12 weeks in the end of the program. While there was no significant difference between pre-test and post test self-esteem points for control group (p>0,05), pre-test and post test scores of experimental group significantly differed (p<0,05). Furthermore, although there was not a significant difference between control groups’ and experimental group’s pre-test self-esteem points (p>0.05), a significant difference appeared between post-test self-esteem points of experimental group and control group (p<0.05). Also, there was not a significant relationship between age and self-esteem. (p>0.05). As a result, recreational activities positively affected self-esteem of university students. That is why it could be suggested that university students should be encouraged to participate in recreational activities and campus areas could be made to suitable to recreational activities